EFFECT OF MICRO FINANCE ON POVERTY REDUCTION OF SMALL SCALE FARMERS OF PAKISTAN - Zaheer Ahmad SAEED (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2013)
This study revealed the impact of micro finance with regard to poverty alleviation, employment generation opportunities, upraise in the standards of living of the small farmers of Pakistan along with the access of such finances and their financial cost. Small farmers often rely on the loans and finance from the formal and informal sources of finance. There is low rate of sustainability in the micro finance sector. These schemes remain for a small time period. Another challenge is that there is a need of replicable and scalable model. There is also a requirement of formalization of informal credit source which count for higher. There is high need of reducing the ambiguities in obtaining the credit from these sources. With respect to agriculture, the proportion of finance should be increase with the proportion to its contribution to the economy. The data for this study has been collected through a selfstructured questionnaire and respondents are small farmers who are availing the micro finance facility for any source; informal, formal or semi – informal. The data collected form 150 respondent from Sahiwal and Multan Region. The data has been analyzed through regression and correlation method with the use of SPSS for checking the relationship and impact of micro finance on the living of poor and employment generation. This paper also concluded that the financial cost of such finances is having significant role on the success of such schemes. The research is a contribution to the financial sector to set their focus according to the quality and quantity of micro credit to the agriculture sector.